General internal medicine and family medicine journals: Comparative study of published articles using bibliometric data - Sebo, Paul (Medicine (Baltimore), 2020)
Like research in general internal medicine, family medicine research can play an important role in improving medical knowledge. We aimed to compare articles published in family medicine journals with articles published in general internal medicine journals. In this bibliometric study, we retrieved 658 randomly selected quantitative articles published in 2016 in 18 high impact factor journals of family medicine and general internal medicine. We extracted the following data: author (gender, number of publications, and place of residence of the first author), paper (number of participants, study design) and journal characteristics (journal discipline, 2015 impact factor). We compared the two groups of articles, using multivariate logistic regressions adjusted for impact factor and intra-cluster correlations. The first author of the articles published in family medicine journals, compared to general internal medicine journals, was more often a woman (OR 2.8 [95%CI 1.8–4.4], P-value < .001), living in the Western world (OR 14.4 [95%CI 6.0–34.4], P-value < .001), and a less experienced researcher (<5 vs >15 publications: OR 2.4 [95%CI 1.5–4.0], P-value .01). In addition, these studies generally included more participants (>1000 vs <100: OR 3.5 [95%CI 1.4–8.6], P-value .02). There was no statistically significant difference in the study design between the two groups of articles (P-value .25). Despite some differences between the two groups of articles, studies published in family medicine journals do not appear to be any less ambitious in terms of study design and sample size than those published in general internal medicine journals.